Training load, neuromuscular readiness, and perceptual fatigue profile in youth elite long-jump athletes - Franceschi, A.; Conte, D.; Airale, M.; Sampaio, J. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To describe and identify individual trends and changes in training load, neuromuscular readiness, and perceptual fatigue measures in 2 youth elite long jumpers, finalists at the European Athletics U18 (Under 18) Championships (athlete A, female, age 16.5 y, long-jump record 6.25 m; athlete B, male, age 16.0 y, long-jump record 7.28 m). Methods: Data were collected from both training sessions and athletics competitions during a 16-week period, divided into a preparation (weeks 1-8) and a competitive phase (weeks 9-16). Training load was computed through training diaries (training time, sprint, jumping, and weights volume). The countermovement jump and the 10-to-5 repeated-jump test were executed on a weekly basis to assess neuromuscular readiness, and perceptual fatigue measures were collected through a wellness questionnaire. Statistical analysis was conducted using a magnitude-based decisions approach. Results: The results highlighted a decrease in training load during the competitive period with moderate to large differences for training time, sprint, and jump volume. Moreover, data showed an upward trend and very likely higher scores in vertical-jump performance across the competitive phase together with a very likely lower perceptual fatigue. Conclusions: This scenario seemed to be favorable to achieve competition performance very close to the personal record during the competitive season. This study provided an example of application of a comprehensive monitoring system with young athletes involved in track-and-field jumping events.